Nutrition of Bacillus brevis ATCC 9999, the Producer of Gramicidin S - Vandamme, E. J. (Antimicrob Agents Chemother, 1976)
The nutrition of the gramicidin S (GS) producer Bacillus brevis ATCC 9999 was studied with respect to growth and antibiotic production. In a complex medium containing yeast extract and peptone, only glycerol, d-fructose, and meso-inositol contributed to growth, whereas other hexoses, pentoses, polyols, polysaccharides, and organic acids were inactive. Glycerol and fructose were inhibitory to GS formation; inositol had no effect. In chemically defined media containing a mixture of five amino acids (glutamine, methionine, proline, arginine, and histidine) necessary for good growth, again only glycerol, d-fructose, and meso-inositol served as effective carbon sources for growth. With respect to antibiotic formation, inositol was much poorer than glycerol or fructose. In the presence of glycerol and the five amino acids, addition of 0.1% l-phenylalanine specifically stimulated GS production. Growth kinetics in this defined medium showed two phases: early and rapid growth at the expense of the amino acid mixture, followed by glycerol utilization after a diauxic lag of 2 to 3 h; inositol utilization suffered a much longer lag period. GS formation was initiated after the diauxic lag. Ammonium sulfate was the best individual nitrogen source, but the combination of the five growth-stimulatory amino acids was more potent for GS production. The level of potassium phosphate influenced GS production. High levels stimulated the growth rate but progressively inhibited GS production. Methionine was the best sulfur source. A defined medium (F3/6) that supported rapid exponential growth (μ = 0.53 h(−1)) followed by progressively slower growth over a 30- to 40-h period was devised containing fructose, six amino acids, and mineral salts. GS formation was initiated as the cells left the exponential growth phase and reached high levels (1,500 mg of GS per liter; 0.19 mg of GS/mg of dry cell weight) after 40 to 50 h of incubation.